Searching for artificial equilibrium points to place satellites above and below L3 in the Sun-Earth system - De Almeida, A. K.; Prado, Antonio F.B.A.; Sanchez, Diogo M.; Yokoyama, Tadashi [UNESP] (My University, 2017)
Regarding practical applications of L3 of the Sun-Earth system, there are few studies with the goal of placing a spacecraft at this point, or in orbit around it. One of the main problems in placing a spacecraft near this equilibrium point is the fact that it is located behind the Sun with respect to the Earth. The Sun would be blocking direct communication between the spacecraft and the Earth. The present research gives several options to solve this problem by using a solar sail to place one or two spacecraft above and/or below the Ecliptic plane. This sail could also be used for the mission itself, to collect energy or particles. By using an adequate size, location and attitude of the solar sail, the equilibrium point can be moved from its original location to allow communications between the spacecraft and the Earth. A preliminary study of a solar sail that uses this strategy is shown here.
Keywords: Celestial mechanics; Occultations; Planets and satellites: general; Space vehicles: instuments